ECONOMIC AND/OR SOCIAL CRISIS (Annual of the Faculty of Philosophy in Skopje, 2009)
Financial crisis that start in USA in 2008 very fast was spread around the globally linked markets transforming itself from financial into global economic crisis. Taking over the real economy the crisis was positioned as limited factor for economic and social survivals. The questions are raised: could the crisis in the further processes will be transformed from financial and economic into social crisis and crisis of the systems. This possible transformation will put in question the basic principles of the real economic’s and everyday activities on which the market economies are based.Which are the possible solutions for solving the crisis and how the impacts of the crisis are considerate from the point of different states? These are the main issues which are presented in this article. Through analysis of the changes of some economic and financial parameters, and also based on the expression of some social situations and risks that become evident could be seen the directions in which the state could be driven in searching for possible solutions.
Keywords: crisis; economic and social; solutions for solving the crisis; systematic impacts and limits